(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Does learning about entrepreneurship really change students’ plans to start their own businesses? How do a student’s desire to be an entrepreneur and their entrepreneurial mindset influence their plans to start a business? Experts and those involved in entrepreneurship have been looking into this topic for a while. To tackle these questions, the authors suggest a model for understanding entrepreneurial intentions. This model is based on the Theory of Planned Behaviour and explores how entrepreneurial education plays a role in this process. Through a method called hierarchical regression analysis with structural equation modelling, it was found that female students studying business are more likely to want to start their own businesses. This points out the significance of having an entrepreneurial mindset and desire, along with the benefits of entrepreneurial education and skills. The research shows that entrepreneurial education, along with other factors such as innovation, control over one’s destiny, willingness to take risks, personal beliefs, confidence in one’s abilities, and societal expectations, has a significant impact on entrepreneurial intentions at a 5% significance level. The research suggests that the government should back entrepreneurship programs to help change students’ perspectives, attitudes, and plans for future entrepreneurial endeavours.